Digital Literacy Initiation Through the Family Literacy Movement for Sogan Elementary School Parents - Novy Trisnani; Anita Dewi Astuti; Wulan Tri Puji Utami; Endah Rahmawati (STKIP Singkawang, 2022)
The progress of knowledge in the educational process is one of the crucial needs that must be met by parents and guardians of students, especially when implementing learning from home as a result of the current Covid-19 pandemic. The Community Service Program with activities to introduce digital-based family literacy movements is one of the efforts to help the community, especially parents, to continue to understand the progress of knowledge to support the education and learning process from home. Outcomes Community service activities that have been carried out at SD Negeri Sogan aim to help improve digital literacy skills in everyday life. The subjects of the service were the guardians of the sixth grade students at SD Negeri Sogan as many as 20 people. The method of implementing service activities is carried out through 3 (three) stages, namely need assessment, implementation, and evaluation of activities. From the results of the evaluation of the implementation of the activities, it can be concluded that 1) it is effective and useful for service participants, namely the guardians of class VI Sogan Elementary School; and 2) there is an increase in the knowledge and understanding of service participants about the digital-based family literacy movement.